BUKU DOKUMENTASI FOTOGRAFI “KELENTENG BOEN SAN BIO” - Martinus Eko Prasetyo Kaparang; Shierly Everlin; Angelina Theresia Eva (Jurnal Bahasa Rupa, 2023)
The temple is a religious building which is a cultural heritage. Being a historical value of Chinese culture, the Temple is a place to honor the ancestors (ash house) and Gods and Goddesses with various kinds of typical Chinese ornaments as well as statues of Gods from Confucian beliefs complete with their distinctive weapons, an altar complete with a place to place incense for worship. Boen San Bio Temple was built in 1689 by Chinese traders. The purpose of designing this book is to introduce the wider community to the history of the construction of the Boen San Bio Temple, as well as to protect Chinese cultural heritage in Indonesia. This research uses descriptive and qualitative methods, research to find accurate information about the history, development, culture of the "Boen San Bio" temple building as well as factual and detailed architecture starting from the main part, to buildings on other sides such as the west side, east side, the north and south sides which maintain photography media to produce photography books in order to maintain one of the Chinese cultural heritage values ​​in Tangerang City in the form of the Boen San Bio Temple building. With the photography book, it is hoped that it will become documentation of introductory information about the Boen San Bio Temple for the first time in Indonesia.